Growing up on facebook - Robards, Brady and Lincoln, Siân (Digital formations, 2020)
"Growing up in the era of social media isn't easy. With Facebook now having existed for more than a decade and a half, young people who have grown up using social media can now look back and see earlier versions of themselves staring back: nostalgic moments with friends from school, reminders of painful breakups, birthdays and graduations, posts that allude to drama with family, experiences of travel, and blurry drunken photos. How do we make sense of our own personal histories inscribed on and through social media? What are the implications for future careers, for public trust in social media companies, and for our own memories? Growing up on Facebook examines the role of Facebook, and other social media platforms that have emerged around Facebook, in mediating experiences of 'growing up' for young people. Based on interviews with the first generation of young people to grow up with social media, the book covers education and employment, love and relationships, family life, and leisure (drinking, travel, and music). It touches on processes of impression management, privacy, context collapse, and control, and raises critical questions about the standards we hold social media platforms to, as they become the guardians of our personal histories. The book will appeal to both academic and general audiences alike. Students and scholars in media and communications, the sociology of youth, and beyond, will find strong connections to the literature and acknowledgement of the methodological detail of the study the book is based on. The themes and issues covered in the book are also of broader interest, and will appeal to people who have themselves grown up in the era of social media, to parents, educators, and anyone interested in how we look back at social media as a personal memory archive"--
https://katalog.adlr.link/Record/0-1680664654